IJCM_303A: Prevalence and Factors associated with treatment-seeking behaviour of Diarrhoea among children under five in India - Arya VR; Giri Anjan Kumar (Wolters Kluwer Medknow Publications, 2024)
Background: Diarrhoea forms a significant public health problem in children under five years of age, especially in developing countries. The 2020 National Health Portal of India report shows 23373520 cases and 6229 deaths from diarrhoeal diseases were recorded across India. Current evidence using nationally representative data on determinants of care-seeking behaviour for Diarrhoea is limited in the Indian context. Hence, the present study complements the existing literature by examining the health-care-seeking behaviour regarding Diarrhoea among Indian children under age five. Objective: To study the prevalence and Factors associated with treatment-seeking behaviour of Diarrhoea among children under five in India Methodology: Study design: Cross-sectional study. Methods: The data for the present study were drawn from the fifth round of the National Family Health Survey (NFHS-5) conducted in 28 states and 8 union territories of India in 2019-21. Out of 222,233 children age less than five years, 16214 children having Diarrhoea were selected to explore the treatment-seeking behaviour. Results: Among children under five years, 7.2% suffered from diarrhoea in the two weeks receding the survey, and 76% sought treatment for Diarrhoea. Conclusion: Mother's schooling is found to be important factor in health care-seeking behaviour. Thus, enhancing mothers' awareness will help advance the healthcare-seeking behaviour.